Bibliometric Analysis of Global Engagement Research: Trends, Prolific Authors, and Impact in Environmental Science and Business & Economics Fields - Maykel Ifan; Edi Purwanto; Jan Pieter Ate; Manlian Ronald A. Simanjuntak (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2023)
Global engagement has become vital to academic research, particularly in economics and environmental science. This bibliometric analysis utilizes Scopus Analyze and VOSviewer to explore trends, prolific authors, and the impact of global engagement research in these fields, identifying research gaps in reputable international databases like Scopus. The study aims to provide insights into the implications of global engagement on society, economy, and environment. Data from 105 papers were collected, with reputable international journals being the dominant source. Findings indicate a rising interest in global engagement research from 2014 to 2023, with the United States leading in contributions, followed by the United Kingdom, Australia, and other countries. Themes prevalent in the research include education and sustainable development, focusing on cross-cultural learning experiences and the need for international cooperation to address global challenges. In environmental science, scholars explore sustainable development, the sustainable ocean economy, and the impact of economic growth on environmental sustainability, seeking to design effective strategies for green technologies and sustainable practices. This study's valuable insights contribute to business, economics, and environmental science, guiding future research and understanding global engagement's implications in various domains while identifying research gaps that offer opportunities for further investigation into novel aspects of global engagement.